Design and baseline characteristics of the AMPLITUDE‐O cardiovascular outcomes trial of efpeglenatide, a weekly glucagon‐like peptide‐1 receptor agonist. Issue 2 (22nd October 2020) - Gerstein, Hertzel C.; Branch, Kelley; Heenan, Laura; Del Prato, Stefano; Khurmi, Nardev S.; Lam, Carolyn S. P.; Pratley, Richard; Rosenstock, Julio; Sattar, Naveed
Abstract: Aim: The effect of the weekly exendin‐based glucagon‐like peptide‐1 receptor agonist efpeglenatide on cardiovascular (CV) outcomes in high‐risk patients with type 2 diabetes (T2DM) with and without chronic kidney disease (CKD) is unknown. Materials and methods: People with T2DM and glycated haemoglobin >7%, ≥18 years old with previous CV disease, or ≥50 years old with CKD [defined as an estimated glomerular filtration rate (eGFR) of 25–59.9 mL/min/1.73 m 2 ], and one or more additional CV risk factors were recruited. Participants were randomized in a 1:1:1 ratio, stratified by current, intended or neither current nor intended use of a sodium‐glucose cotransporter‐2 (SGLT2) inhibitor to receive weekly injections of efpeglenatide (4 mg or 6 mg) or masked placebo. The primary outcome is a major adverse CV event defined as non‐fatal myocardial infarction, non‐fatal stroke or CV death. Secondary outcomes include a composite kidney outcome (new onset macroalbuminuria with an increase from baseline of ≥30%, sustained 40% decrease in eGFR, renal replacement therapy, or sustained eGFR <15 mL/min/1.73 m 2 ). The trial will continue until ≥330 participants have had a major adverse CV event outcome and the sample size was based on accruing enough outcomes to detect non‐inferiority of efpeglenatide versus placebo. Results: Recruitment of 4076 participants (33% women, mean age 64.5 years) occurred between 11 May 2018 and 25 April 2019 at 344 sites in 28 countries. Mean baseline glycated haemoglobin was 8.9% (1.5), 31.6% had an eGFR <60 mL/min/1.73 m 2, 89.5% had previous CV disease and 15.0% were on an SGLT2 inhibitor. Conclusions: The results of the AMPLITUDE O trial will inform the use of exendin‐based glucagon‐like peptide‐1 receptor agonist to people with T2DM and high CV risk, with and without CKD, in the presence and absence of an SGLT2 inhibitor.